The effect of blooket-assisted RADEC learning model on students' metacognitive ability - Hella Jusra; Niki Khoirotunnisah (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2026)
The purpose of this research was to investigate the influence of the RADEC learning model by implementing games in learning, specifically Blooket, on students' metacognitive capacities. This study utilized a quasi-experimental design featuring a non-equivalent control group, involving 62 tenth-grade students from high schools in Jakarta during the 2025/2026 academic year. A posttest instrument intended to evaluate students' metacognitive skills was utilized as the principal assessment tool. The data were analyzed using descriptive statistics and an independent samples t-test. The findings showed that the experimental class achieved a higher mean score compared to the control class. The hypothesis testing results also indicated a statistically significant difference between the two groups. The results demonstrate that the application of the Blooket-supported RADEC learning paradigm positively influenced students' metacognitive skills. The efficacy of the RADEC learning paradigm is linked to its organized learning phases, which promote student engagement in planning, monitoring, and assessing their cognitive processes during mathematics activities. Moreover, the incorporation of Blooket as a technology-driven educational platform fosters a more participatory and stimulating learning atmosphere through gamification and prompt feedback. Consequently, the Blooket-supported RADEC learning paradigm can function as an innovative and successful option to enhance students' metacognitive skills in mathematics education.